(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The text inherits from the history of human civilization of "The same completely inclusive faith with its laws of the Trinity" that expressed in various ways across civilization and cultures. Examples of this inheritance include the Trinity of Greek and Roman philosophy; the representation of "Faith in God and Its Trinity Laws" through the "Cross" in the Bible; the Quran’s representation of "Faith in Allah and Its Laws of Allah’s Star and Moon"; the Buddhist scriptures’ representation of "Faith in Buddha and Its Laws of Trilakāya" through "The Revolving Cross"; and Chinese philosophy in Tao Te Ching and The Book of Change, which shares the concept of "Faith in Tao and (Entailment of The) One Yin, (Presenting of The) One Yang, called The Tao (Laws)" symbolized by "Yin Yang Ball". Additionally, various faiths represent their Trinity-Laws using symbols such as “Hermaphrodite Baphomet” or “Pentagram and circle compounded together as one", facilitating communication between Christianity and Islam. However, human societies, groups, and individuals often fail to integrate human knowledge and experiences fully, resulting in a partial understanding of these concepts (even if Awakened monks and hermits exist, they might face interdisciplinary or language barriers hindering the spread of truth).Start open “The Same Completely Inclusive Scientific Faith with Its Principium of Natural Laws of The Compounding-Corresponding-Trinity”which relies on “The Three Major Natural Complementary Principles” that build up by “Laws of Personality” which also is “Principium of Commonality”. And are fundamentally compounding and corresponding, clarifying the existing ways and existing relationships of the trinity of all things. Lay the foundation for humanity to achieve reconciliation, reach consensus, and jointly building "The Everbright Era of Earth Human Democratic Federation’s Scientific Social Public Morality Mature Self-Consistent Guarantee Node-System". And escorting human beings to advance to the ranks of intelligent life in the universe that consciously abides by the laws of the universe.